(untitled) (UNED Research Journal, 2020)
Introduction: Mosquitoes are potentially regarded as one of the most deadly animals in the world as they are known to vector a number of vital diseases. The faunistic composition and prevalence of these mosquitoes are dependent on the characteristics of the larvae habitats. Objective: In this study we surveyed the mosquito larvae in relation to the characteristics of their various microhabitats with the aim of determining how the habitats influence the composition, abundance and distribution of the mosquito larvae on Obafemi Awolowo University, Ile - Ife campus. Methods: We did mosquito larvae sampling monthly between 07: 00 and 10:00 for six months (August, 2017 - January, 2019) using standard dipping method. The various microhabitats sampled included; ground pools, discarded containers, drainage channels and tree holes in each of the study sites. Results: We identifies seven species distributed in three genera as following; Anopheles spp. (Anopheles gambiae, Anopheles funestus); Aedes spp. (Aedes aegypti, Aedes albopictus); Culex spp. (Culex pipiens, Culex quinquefasciatus, Culex poicilipe). Culex was the dominant and most abundant genera as it accounted for 48% of the entire collection. Mosquito larvae were significantly (p<0,05) more abundant in the dry season than in the wet season. The highest abundance of mosquitoes was recorded in Akintola Hall as it accounted for 50,1% of the entire collection. Findings in this study also revealed that drainage channels in the study sites accounted for the highest abundance of mosquitos. A total of 277 ind. were collected in the various drainage channels in the study sites and this represented 45% of the entire collection while Leaking pipes and Ground pools accounted for 89 (15%) and 87 (14%) individuals respectively. We collected majority of the mosquitoes near dwellings thus suggesting that the species identified in this study have affinity for humans and their dwellings. Conclusion: We suggest that un-kept drainage channels, leakages and discarded domestic containers littered around the study sites are possible contributing factors to the enormous breeding sites available to mosquitoes. Elimination of such breeding sites can effectively mitigate the survival and prevalence of mosquitoes in the area.